Robotic Process Automation with Blue Prism Quick Start Guide Create Software Robots and Automate Business Processes. - Mei Ying, Lim (Packt Publishing Ltd, 2018)
Robotic process automation is a form of business process automation where user-configured robots can emulate the actions of users. Blue Prism is a pioneer of robotic process automation software, and this book gives you a solid foundation to programming robots with Blue Prism. If you've been tasked with automating work processes, but don't know ...